Culture change and lessons learned from ten years in the VA centers of excellence in primary care education - William G. Weppner; Mamta K. Singh; Joyce E. Wipf; Rebecca Shunk; LeChauncy Woodard; Rebecca Brienza (BMC Medical Education, 2024)
Abstract Background Team-based care is critical to achieving health care value while maximizing patient outcomes. Few descriptions exist of graduate-level team training interventions and practice models. Experience from the multisite, decade-long Veterans Affairs (VA) Centers of Excellence in Primary Care Education provides lessons for developing internal medicine training experiences in interprofessional clinical learning environments. Methods A review of multisite demonstration project transforming traditional silo-model training to interprofessional team-based primary care. Using iterative quality improvement approaches, sites evaluated curricula with learner, faculty and staff feedback. Learner- and patient-level outcomes and organizational culture change were examined using mixed methods, within and across sites. Participants included more than 1600 internal medicine, nurse practitioner, nursing, pharmacy, psychology, social work and physical therapy trainees. This took place in seven academic university-affiliated VA primary care clinics with patient centered medical home design Results Each site developed innovative design and curricula using common competencies of shared decision making, sustained relationships, performance improvement and interprofessional collaboration. Educational strategies included integrated didactics, workplace collaboration and reflection. Sites shared implementation best practices and outcomes. Cross-site evaluations of the impacts of these educational strategies indicated improvements in trainee clinical knowledge, team-based approaches to care and interest in primary care careers. Improved patient outcomes were seen in the quality of chronic disease management, reduction in polypharmacy, and reduced emergency department and hospitalizations. Evaluations of the culture of training environments demonstrated incorporation and persistence of interprofessional learning and collaboration. Conclusions Aligning education and practice goals with cross-site collaboration created a robust interprofessional learning environment. Improved trainee/staff satisfaction and better patient care metrics supports use of this model to transform ambulatory care training. Trial registration This evaluation was categorized as an operation improvement activity by the Office of Academic Affairs based on Veterans Health Administration Handbook 1058.05, in which information generated is used for business operations and quality improvement (Title 38 Code of Federal Regulations Part 16 (38 CFR 16.102(l)). The overall project was subject to administrative oversight rather Human Subjects Institutional Review Board, as such informed consent was waived as part of the project implementation and evaluation.